An experimental investigation of the role of safety-seeking behaviours in the maintenance of panic disorder with agoraphobia. - Salkovskis, P; Clark, D; Hackmann, A; Wells, A; Gelder, MG (1999)
This study evaluates the hypothesis that safety-seeking behaviours play an important role in maintaining anxiety because they prevent patients from benefiting from disconfirmatory experience. Patients suffering from panic disorder with agoraphobia carried out a behaviour test, closely followed by an experimental session, which included a brief (15 min) period of exposure during which participants either stopped or maintained within-situation safety-seeking behaviours. When the behaviour test was repeated within two days, patients who had stopped their safety-seeking behaviours during the experimental session showed a significantly greater decrease in catastrophic beliefs and anxiety than those who had maintained safety-seeking behaviour. This difference was also reflected in questionnaires measuring clinical anxiety. These results are consistent with the cognitive hypothesis.